UPAYA MENINGKATAN HASIL BELAJAR MELALUI MODEL PEMBELAJARAN TEAM GAME TOURNAMENT (TGT) PADA PENDIDIKAN PANCASILA SISWA KELAS IV SDN SUMURGUNG 1 TUBAN - Icha Arofatin Kusnia; Wendri Wiratsiwi (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study began with the low achievement of student learning outcomes, which was caused by the lack of innovative learning models implemented by teachers and the dominance of teacher-centered learning approaches. This situation leads to reduced student engagement during the learning process.This study aims to improve student learning achievement in the Pancasila Education subject by implementing the Team Games Tournament (TGT) learning model for fourth grade students at SDN Sumurgung 1 Tuban in the 2024/2025 academic year. The research employs the Classroom Action Research (CAR) approach. In the implementation of cycle I, the average student score was 71.4, with a learning completion rate of 42.8%. After improvements were made in cycle II, the average student score increased to 98.5, and the classical learning completion rate reached 98.5%. Based on the results of data analysis, it can be concluded that the application of the Team Games Tournament (TGT) learning model is effective in improving student learning outcomes in the Pancasila Education subject in fourth grade at SDN Sumurgung 1 Tuban.